The Influence of School’s Culture and Organizational Commitment on Teacher’s Performance in State High Schools - Hidayatullah, Sanul (PPSDP International Journal of Education, 2023)
The purpose of this study was to determine the effect of school’s culture and organizational commitment on teacher’s performance in public elementary schools in Tanjung Lubuk subdistrict, Ogan Komering Ilir district.This study was conducted on teachers in Tanjung Lubuk District, Ogan Komering Ilir Regency. The sample size was taken as many as 43 teachers in Tanjung Lubuk District, Ogan Komering Ilir Regency. The data was carried out by distributing questionnaires using a 5-point Likert scale to measure 67 statement items. The analysis technique used is multiple linear regression analysis. The results show that organizational commitment and school’s culture simultaneously have a significant effect on teacher’s performance. Organizational commitment has a partial and significant effect on teacher’s performance. School’s culture has a partial and significant effect on teacher’s performance.